Short Story for Developing Students Vocabulary in Reading Comprehension of Narrative Text in Banten - Syafrizal Syafrizal; Tosi Rut Syamsun (Journal of Linguistics, Literacy, and Pedagogy, 2022)
This research was conducted to analyze of short stories for developing students’ vocabulary in reading comprehension of narrative text in the tenth grade of Junior High School. Reading comprehension in English needs to be designed to prepare them to face global competition. Learning vocabulary for students is highly important because by reason of knowing mastery of vocabulary we can comprehend reading English handily. The research was conducted to investigate reading comprehension learning using short stories to find out students' opinions about using short stories as a medium of reading comprehension to assist them in writing narrative texts. The participants of this study were 10 students from tenth grade A, namely (male = 5, female = 5) in Junior High School. This study was designed using descriptive qualitative research because the data were taken from observations, interviews, and documentation. The findings of this study indicate that short stories as a teaching method can be used to develop students' reading comprehension.© 2022 JLLP and the Authors - Published by JLLP.